Older males whistle better: Age and body size are encoded in the mating calls of a nest-building amphibian (Anura: Leptodactylidae) - Stănescu, Florina; Márquez, Rafael; Cogălniceanu, Dan; Marangoni, Federico (Frontiers in Ecology and Evolution, 2022)
Courtship acoustic displays in anuran amphibians are energetically costly and risky, but have a major role in mating success since they encode relevant information regarding the caller’s identity and status. Age and size are essential traits shaping fitness, reproductive success and life-history strategies, and thus are expected to also have a role in courtship displays. We tested this assumption in a species of nest-building frogs, Leptodactylus bufonius, in northern Argentina. We conducted the first detailed quantitative description of the males’ mating calls and assessed the effects of biological traits (i.e., body size parameters and individual age) and local climate (i.e., air temperature and humidity) on the main acoustic features of these calls (i.e., call duration, inter-call duration, dominant frequency and dominant frequency modulation). The calls were short (mean±SE, 0.163±0.004 s), whistle-like, single notes with harmonic structure. The dominant frequency (1381.7±16.2 Hz) decreased with arm length (χ2=5.244, df=1, p=0.022) and had an upwards modulation (456.4±11.0 Hz) which increased with age (χ2=4.7012, df=1, p=0.030). Call duration and dominant frequency were the most static parameters at intra-individual level, indicating their role in individual recognition. Temperature and humidity shaped the temporal acoustic parameters, and the dominant frequency. Our findings suggest that the acoustic features of the mating calls in amphibians could promote female mate choice in relation to both size and age and open up new questions for future research: are females more attracted to older males, and what are the specific costs and benefits? We suggest that mating calls may direct female preferences towards males of certain size and age classes, ultimately shaping the life-history strategies in a given population. Finally, we found discrepancies in the mating calls of L. bufonius recorded from Corrientes and those previously described from other populations, which suggests that multiple species may have been recorded under the same name.